Medical treatment of allergy in children with recurrent or chronic sinusitis - Abdollahi-Fakhim, Shahin (Niger Med J, 2014)
BACKGROUND: Diagnosis and treatment of chronic and recurrent sinusitis in children is of potential importance and many factors can havean influence on it. This study assessed the chronic and recurrent sinusitis and affecting factors, as well as the role of allergy in its course and treatment in children. MATERIALS AND METHODS: A total of 106 children with the diagnosis of chronic or recurrent sinusitis, referred to specialty clinics of otolaryngology and allergy of Tabriz Children Educational-Medical centres since 2010 to 2012, were enrolled. The history and physicalexamination findings were recorded for all patients and allergy Prick test was done for all. Response to treatment was evaluated during the follow-up visits. RESULTS: The mean age of studied patients was 6.5 ± 2.9 years. Of all the patients, 54 (50.9%) were male and 52 (49.1%) were female. Skin Prick test was positive in 69.8%. Response to treatment was seen in 86.8% of the patients while 7.5% did not have any favourable outcome. Anti-allergic treatment caused better outcomes in patients with positive Skin Prick test than those with negative results. CONCLUSION: The prevalence of allergic disease in children with chronic or recurrent sinusitis is considerable and anti-allergic treatments can result infavourable therapeutic outcomes in children with sinusitis, especially with positive skin prick test results.